Konsep Wanita Shalihah Dalam Tafsir Al-Azhar - Resviana Resviana; Hasiah Hasiah; Desri Ari Enghariano (Jurnal El-Thawalib, 2021)
One of the missions of Islam is to glorify women and put them in a respectable position, so that they can reach the status of pious women. Actually, the mission of Islam has been achieved in the time of the prophet Muhammad SAW and how many decades after that still make the Qur’an as a way of the life. However, the reality of life in modern times today shows an alarming fact. Many Muslim women have experienced moral decadence. Many Muslim women today fall into acts that are prohibited by religion, such as courtship, adultery, and others. Sinful acts like this cause them to be far from the category of pious women. Whereas if they were asked to choose to be a pious woman or a pious woman, of course the answer from the bottom of their hearts would be to choose a pious woman. Women are glorified in Islam because of their role and position as child, wife, and mother. Because Islam really maintains the dignity of a woman well. The most high ranking woman is a pious woman who always istiqamah in carryng out all the commands of Allah and staying away from all the prohibitios. The formulation of the problem of this research is how the concept of pious women in the interpretation of Al-Azhar, the aim is to find out the aim is to find out the concept of pious women in the interpretation of Al-Azhar. This type of research is library research, namely research through library research, gathering techniques by searcing for verses about pious women. Based on the interpretation approach, which is done by the workings of the tahlili method. The results of this study are shalihah women can be said to be women who maintain their eyes, are consistent in covering their genitals, women who have strong personalities, women who are obedient and intelligent, and women who maintain their chastity.